3...2...1... action! the female gender roles portrayed in the comedy broadcast program Modern Family - Garcia, Claudette Amponin 1993- (2014)
"This study focused on how the female gender roles are portrayed by the media in the comedy broadcast program Modern Family to define the blurred lines caused by the thick facade of humor covering the sensitive area of discrimination and stereotyping. Modern Family, a sitcom that started airing in 2009 and which focuses on three contemporary biologically-related American families, was used for the notable presence of its female characters and their portrayals. This study also aimed to situate these kinds of female portrayal beside the gender role portrayals in families in the society to look at the point-of-view from which the people behind the program possibly reflected what they are showing. This study initially did purposive sampling to narrow down the episodes into those with significant presence of women only and then studying them using textual analysis under the guidance of feminism. The study found out that the female characters in the show are placed in a subordinate position, discriminated against and are constantly thrown into circumstances that hinder them from going beyond their traditional roles and reaching their full potential."